Thinking about downlink of resolution advisories from airborne collision avoidance systems. - Brooker, Peter (Ashgate Publishing, 2004)
One of the open questions about Airborne Collision Avoidance Systems (ACAS) is whether Resolution Advisory (RA) information should be automatically downlinked to the display of the controller handling the aircraft involved. The aim here is to see if a clear pathway for decision-makers can be derived from rational assessment using general safety principles and Human Factors guidelines, plus readily available data. Situational awareness principles indicate that RA downlink should be as simple as possible, consistent with improving safety, preferably using an existing display type. The proposed method for assessing the potential benefits and disadvantages of RA downlinking uses Airproxes, mainly because they represent occasions in which situational awareness is impaired, and a structured analysis of the effects of downlinking on the various kinds of Airprox, controller action and pilot report.